The Role of Collaborative Learning in Higher Education to Improve Students’ Entrepreneurial Commitment - Margunani, Siti Nurjanah, Inaya Sari Melati (International Journal of Advanced Science and Technology, 2020)
This study aimed to analyze the direct and indirect effects of collaborative learning on entrepreneurial commitment through entrepreneurship and entrepreneurial culture. This research was carried out by using a causal design. Population was 903 Entrepreneurship students studying in the academic year 2016-2017 (even semester). The sample was determined by referring to the Isaac and Michael Table with an error of 1%. The unit of analysis of this study was 385 students participating in entrepreneurship lectures. Research data were analyzed by path analysis techniques. The path model was tested by the goodness of fit model. The results of this study indicated that collaborative learning had a strategic role in strengthening students’ entrepreneurial commitment, strengthening mastery of students' knowledge and skills in the field of entrepreneurship and strengthening the development of entrepreneurial culture among students. Keywords: Collaborative Learning, Entrepreneurship, Culture, Commitment